2019
DOI: 10.3390/polym11122064
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Mechanical Properties of the Poly(oxymethylene) Composites Reinforced with Glass Fibers under Dynamical Loading

Abstract: The paper evaluated the possibility of potential reinforcing of poly(oxymethylene) (POM) by glass fiber and the influence of fiberglass addition on mechanical properties under dynamic load. Four types of composites with glass fiber and another four with carbon fiber were produced. The fiber content ranged from 5% to 40% by weight. In the experimental part, the basic mechanical and fatigue properties of POM-based composites were determined. The impact of water absorption was also investigated. The influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…4 GPa. We observed a similar tendency in our previous research, where Poly(oxymethylene) (POM) with the addition of glass and carbon fibers (content from 0 to 40 wt.%) was tested [ 21 ]. As the content of glass fibers increases, the Young’s modulus obtained during cyclic loading increases (for content of 20 wt.% of fibers the Young’s modulus was about 3 times higher than for neat POM).…”
Section: Resultssupporting
confidence: 84%
“…4 GPa. We observed a similar tendency in our previous research, where Poly(oxymethylene) (POM) with the addition of glass and carbon fibers (content from 0 to 40 wt.%) was tested [ 21 ]. As the content of glass fibers increases, the Young’s modulus obtained during cyclic loading increases (for content of 20 wt.% of fibers the Young’s modulus was about 3 times higher than for neat POM).…”
Section: Resultssupporting
confidence: 84%
“…19,20,22,23 In this study, 11 wt% glass fiber reinforcement was used taking into account the work of Faudree et al 21 In addition, up to 40 wt% of short glass fibers can be used efficiently in polymer composites. 24,25 In this study, 40 wt% of glass fiber was used to improve the mechanical properties of a BMC composition (D1). The difference between the D1 sample used in this study and the other samples is that the glass fiber content is much higher than the other samples.…”
Section: Methodsmentioning
confidence: 99%
“…They pointed out that MWCNTs reduced the induction time of crystallization and improved the crystal growth rate and crystallization temperature of POM. Furthermore, Kuciel determined the influence of fiber geometry on the mechanical behavior of fiber-reinforced POM-based composites of various diameters [14]. The results showed that the addition of up to 10 wt.% fiberglass increased the tensile properties and impact strength more than twice, and the ability to absorb energy also increased in relation to neat POM.…”
Section: Introductionmentioning
confidence: 99%